The Implications of the Transition from GRI Standards 2016 to GRI Standards 2021 for Firm Value: Evidence from Indonesian Energy and Basic Materials Companies - Ria Putri Darmayati; Sari Indah Oktanti Sembiring (CV Edujavare Publishing, 2026)
The transition from the Global Reporting Initiative (GRI) Standards 2016 to GRI Standards 2021 represents a significant development in sustainability reporting by introducing revised Environmental, Social, and Governance (ESG) disclosure requirements intended to improve the quality, consistency, and comparability of sustainability information. However, empirical evidence on whether this transition strengthens the relationship between ESG disclosure and firm value remains limited, particularly in emerging markets. This study examines the implications of the transition from GRI Standards 2016 to GRI Standards 2021 for firm value by comparing ESG disclosure measured under the two reporting standards. A quantitative approach was employed using secondary data from energy and basic materials companies listed on the Indonesia Stock Exchange during the 2019–2024 period. ESG disclosure was measured using disclosure indices constructed under GRI Standards 2016 and GRI Standards 2021, while firm value was proxied by Tobin's Q. Panel data regression analysis was applied to examine the proposed relationships. The findings reveal that ESG disclosure measured under both GRI Standards 2016 and GRI Standards 2021 has no significant effect on firm value. Furthermore, no significant difference was found between the two reporting standards in explaining firm value. These findings indicate that the transition from GRI Standards 2016 to GRI Standards 2021 has not strengthened the informational role of ESG disclosure in influencing market valuation among energy and basic materials companies. This study contributes to the sustainability reporting literature by providing empirical evidence that revisions to reporting standards alone are insufficient to enhance the informational usefulness of ESG disclosure in the Indonesian capital market